Analysis of educational innovation proposals in the Practicum of the Degree in Pedagogy - Esteban Vázquez-Cano; M.ª Luisa Sevillano García; Francisco De Pedro Sotelo (Universidad de La Rioja, 2019)
In this article, a study is presented in which university students' conceptions about educational innovation are analyzed through their work in the Pedagogy Practicum at UNED. The participating sample consists of 170 students belonging to the fourth course of the Degree in Pedagogy during the 2016/17 academic year. The research has been developed from a double qualitative perspective: text analysis of the final report of the subject and the analysis of discussion forums of UNED digital platform. For this purpose, the use of the Atlas-Ti program and the reticular-categorial approach of social network analysis with the application of UCINET have been used. The most significant results show that the five areas in which students have identified and proposed a greater number of actions are the following: school coexistence (n = 56), harassment (n = 93), teacher training (n = 87), active methodologies (n = 88) and education in values (n = 32). In this sense, the study provides an alternative vision to innovation through the eyes of the student of the last year of the Degree in Pedagogy, as a result of their professional practices.